2021
DOI: 10.3390/nu13030728
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effects of Dietary Polyphenols

Abstract: Functional and nutraceutical foods provide an alternative way to improve immune function to aid in the management of various diseases. Traditionally, many medicinal products have been derived from natural compounds with healing properties. With the development of research into nutraceuticals, it is becoming apparent that many of the beneficial properties of these compounds are at least partly due to the presence of polyphenols. There is evidence that dietary polyphenols can influence dendritic cells, have an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
109
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(140 citation statements)
references
References 164 publications
0
109
0
4
Order By: Relevance
“…Additionally, NO and ROS contents in the FFVP group were significantly lower than that of the FVP at 100 µg/mL ( p < 0.01). The previous studies confirmed that polyphenols with antioxidant capacities could effectively clear the harmful ROS and inhibit antioxidant damage by reducing ROS secretion [ 26 ]. The effect of FVP and FFVP on phagocytosis in RAW264.7 cells is exhibited in Figure 6 .…”
Section: Resultsmentioning
confidence: 79%
“…Additionally, NO and ROS contents in the FFVP group were significantly lower than that of the FVP at 100 µg/mL ( p < 0.01). The previous studies confirmed that polyphenols with antioxidant capacities could effectively clear the harmful ROS and inhibit antioxidant damage by reducing ROS secretion [ 26 ]. The effect of FVP and FFVP on phagocytosis in RAW264.7 cells is exhibited in Figure 6 .…”
Section: Resultsmentioning
confidence: 79%
“…Polyphenols are powerful immunomodulatory, anti-inflammatory, and antiviral agents [ 29 , 41 , 42 ]. Not less important, polyphenols have an established role not only in determining one’s inflammatory status [ 43 ] but also in preventing aging [ 44 ], which is one of the main risk factors for severe COVID-19. The immunomodulatory activity of polyphenols has supported their experimental use as therapeutic tools in different acute and chronic inflammatory disorders, including ALI [ 45 ], cardiovascular diseases [ 46 ], obesity, diabetes [ 47 , 48 ], and cancer [ 49 ].…”
Section: Polyphenolsmentioning
confidence: 99%
“…Tiene una envoltura lipídica con tres proteínas ancladas en ellas: E (envoltura), M (membrana) y S (spike), que le da la apariencia de corona, además su tiempo de incubación promedio es de 5 a 14 días (Díaz-Castrillón y Toro-Montoya, 2020). A su vez, la infección ocasionada por el SARS-CoV-2 se asocia con problemas en vías respiratorias que van desde síntomas leves a severos que pueden desencadenar en la muerte (Butlera y Barrientos, 2020;Shakoor et al, 2021).…”
Section: Covid-19 Y Su Impacto En La Salud Emocionalunclassified
“…Vitamina D La Vitamina D (VD) es un precedente de la hormona esteroidea que es esencial para el organismo humano. Uno de sus orígenes es endógeno, cuando se expone a la radiación ultravioleta B (UVB) en la epidermis de la piel en donde se transforma en colecalciferol, el cual se hidroxila en el hígado para formar 25hidroxivitamina D, que se transforma en la hormona 1,25-hidroxivitamina la cual termina en el riñón como Calcitriol (Shakoor et al, 2021); o exógeno por medio de la ingestión de verduras (vitamina D2, ergocalciferol) o de origen animal (colecalciferol) (Bizzaro, Antico y Fortunato, 2017). En 2019 se realizó un ensayo aleatorizado con placebo en donde se investigó si la suplementación en personas mayores de 65 años mejoraría la RI para evitar el riesgo de contagio por influenza; se dividieron los voluntarios en dos grupos: el primero con un nivel sérico de VD ≥30 ng/mL y el segundo con un nivel <30 ng/mL.…”
Section: Probióticosunclassified
See 1 more Smart Citation